“Ageism” Is Associated With Self-Reported Multidimensional Frailty in Community-Dwelling Older Subjects: A Population-Based Study - Zora, Sabrina; Cella, Alberto; Poli, Stefano; Veronese, Nicola; Zini, Elena; Giannoni, Paola; Pandolfini, Valeria; Torrigiani, Claudio; Pilotto, Alberto (Frontiers in Medicine, 2022)
Ageism is a stereotyping, prejudice and discrimination against people, based on age. Ageism may impact the quality of life and the care of older people, a problem that can be greater when the older person is ‘frail’. However, few studies explored the role of frailty as a factor related to ageism. The aim of this study was to assess the association between perceived age discrimination (PAD), i.e. ageism, and multidimensional frailty in a cohort of community-dwelling older adults. We enrolled 1337 community-dwelling subjects over-65 years that filled out a structured questionnaire to collect psycho-socio-economic and behavioral information. Multidimensional frailty was assessed by the SELFY-Multidimensional Prognostic Index Short-Form (SELFY-MPI-SF). PAD, over the past five years, was assessed based on explicit criteria. Overall, 83 out of 1337 participants (6.2%) reported PAD. These subjects were older, more frequently women, with greater economic difficulties, lower level of cultural fruition, social network and psychological well-being, and a greater degree of frailty compared to their counterparts. After adjustment for age and gender, multidimensional frailty (SELFY-MPI-SF score) and negative affectivity were the two only ‘predictors’ significantly associated with PAD (SELFY -MPI-SF, Odds Ratio: 1.19, 95%CI: 1.029-1.370; PANAS negative: Odds Ratio: 1.06, 95%CI: 1.033-1.099). In conclusion, self-reported frailty and negative affectivity are independently associated with PAD in community-dwelling older people. Interventions to prevent and treat frailty could be useful to reduce ageism and improve the well-being of the older people.